2007
DOI: 10.21236/ada473519
|View full text |Cite
|
Sign up to set email alerts
|

Total and Differential Sputter Yields of Boron Nitride Measured by Quartz Crystal Microbalance and Weight Loss (Preprint)

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
(55 reference statements)
3
10
1
Order By: Relevance
“…Yield value increases with the increment in the beam energy; another notable thing is that sputter yield values are changing with angles of beam incidence; this heads towards that sputtering yield is a function of beam incident angle. On the other side, from figure 4 one can notice that for all energies with beam incident angle 0 • (surface normal), sputtering yield profiles are symmetric, this is what Sigmund claimed and same kind of profiles are reported; 1,6,11,13,[20][21][22][23] going further with oblique beam incident angles, sputter yield profile turns to asymmetric in the forward direction. At low energy of 100 eV i.e.…”
Section: E Qcm Data Validationsupporting
confidence: 72%
See 1 more Smart Citation
“…Yield value increases with the increment in the beam energy; another notable thing is that sputter yield values are changing with angles of beam incidence; this heads towards that sputtering yield is a function of beam incident angle. On the other side, from figure 4 one can notice that for all energies with beam incident angle 0 • (surface normal), sputtering yield profiles are symmetric, this is what Sigmund claimed and same kind of profiles are reported; 1,6,11,13,[20][21][22][23] going further with oblique beam incident angles, sputter yield profile turns to asymmetric in the forward direction. At low energy of 100 eV i.e.…”
Section: E Qcm Data Validationsupporting
confidence: 72%
“…Due to sputter erosion, material from the channel wall remove and eventually exposes the underlying magnetic yoke, causing the magnetic field profile to be altered and the end of life to be reached. 1,[5][6][7][8][9][10][11] To investigate this important issue of ceramic wall erosion, a facility is developed equipped with Kaufmann Ion source, rotating Sputtering Quartz Crystal Microbalance (SQCM) Sensor and UHV load-lock arrangements for measuring in-situ volumetric sputtering yield, total sputtering yield (SY), and trajectory of the eroded anode wall material. For sputter yield measurement, couple of techniques have been reported that includes weight loss, 11,12 cavity ring-down spectroscopy (CRDS), 13,14 Rutherford backscattering (RBS), 15,16 Quartz Crystal Microbalance (QCM), 11,17,18 and mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The right of Figure 4 also shows BN sputter yields by QCM and weight loss from our past work 4,7,37,38 as well as measurements from other researchers [39][40][41][42][43] . The sputter yield from QCM measurements at CSU are plotted such that the lower reach of each error bar represents the lower possible bound of BN yield (i.e.…”
Section: B Results and Discussionmentioning
confidence: 94%
“…3,5 Weight loss is also regularly used to measure sputter yield. [6][7][8] Profilometry require extended run times (weeks to months) to obtain accurate results, which translates to large amount of resources and time spent. Parametric studies for these two diagnostics are very difficult for any but the largest institutions to carry out and the test matrix must be picked out carefully beforehand with little margin for error.…”
Section: Introductionmentioning
confidence: 99%
“…2L c θ 2nLcos c ∆υ F ≈ = (8) where δυ is the spectral width of the individual resonance mode, ∆υ F is the frequency spacing between resonance peaks (also called the free spectral range), F is the cavity finesse, R M is the mirror reflectivity, n is the refractive index of the medium between the mirrors, and θ is the angle of incidence with respect to the mirror surface normal. Both n and cos θ are typically equal to 1.…”
Section: Introductionmentioning
confidence: 99%